2015
DOI: 10.1016/j.atherosclerosis.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

A score including ADAM17 substrates correlates to recurring cardiovascular event in subjects with atherosclerosis

Abstract: a b s t r a c tObjective: Atherosclerosis disease is a leading cause for mortality and morbidity. The narrowing/rupture of a vulnerable atherosclerotic plaque is accountable for acute cardiovascular events. However, despite of an intensive research, a reliable clinical method which may disclose a vulnerable patient is still unavailable.Approach and results: We tested the association of ADAM17 (A Disintegrin and Metallo Protease Domain 17) circulating substrates (sICAM-1, sVCAM-1, sIL6R and sTNFR1) with a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…In this study, we found that gene silencing of TACE markedly decreased the serum levels of sTNF-α, sICAM-1, sVCAM-1 and sMCP-1 with the most significant reduction of sTNF-α, suggesting that TNF-α is likely the most important substrate of TACE. Previous studies found that the deficiency of TNF-α in ApoE −/− mice reduced the lesion size of atheroma 27 , and a recent elegant study by Federici M’s group clearly demonstrated that patients with a higher ADAM 17 score including sICAM-1 and sVCAM-1 exhibited increased cardiovascular events 28 . The present study revealed the independent role of sTNF-α and sICAM-1 in plaque vulnerability in our animal model, which lent support to Federici M’s study.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we found that gene silencing of TACE markedly decreased the serum levels of sTNF-α, sICAM-1, sVCAM-1 and sMCP-1 with the most significant reduction of sTNF-α, suggesting that TNF-α is likely the most important substrate of TACE. Previous studies found that the deficiency of TNF-α in ApoE −/− mice reduced the lesion size of atheroma 27 , and a recent elegant study by Federici M’s group clearly demonstrated that patients with a higher ADAM 17 score including sICAM-1 and sVCAM-1 exhibited increased cardiovascular events 28 . The present study revealed the independent role of sTNF-α and sICAM-1 in plaque vulnerability in our animal model, which lent support to Federici M’s study.…”
Section: Discussionmentioning
confidence: 98%
“…Research on sIL6R is inconsistent, with two case control studies displaying no difference in sIL6R levels between ischemic stroke cases and controls whereas levels of IL6 were higher in cases (160,178). Moreover, in subjects with manifest CVD, sIL6R showed no association with recurrent CVE while in post-MI patients, high circulating levels of sIL6R were associated with increased risk of recurrent CVE (151,179). Levels of sgp130 have been demonstrated to be transiently reduced after stroke and to correlate positively with blood pressure and carotid intima media thickness in stroke patients (160,180).…”
Section: Interleukin 6 Trans-signalling In Large Vessel Cerebrovasculmentioning
confidence: 99%
“…ADAM17 activity is correlated to adverse clinical outcomes in acute coronary atherosclerosis (Satoh et al, 2008 ; Gutiérrez-López et al, 2011 ; Rizza et al, 2015 ). An important group of substrates for ADAM17 includes adhesion molecules such as ICAM-1 (intercellular adhesion molecule-1), VCAM-1 (vascular cell adhesion molecule-1), L-selectin, and others.…”
Section: Adam17-mediated Cytokines and Adhesion Molecules Signalingmentioning
confidence: 99%
“…Local over-activity of ADAM17 may weaken atherosclerotic plaques, causing its rupture. In this context, Rizza et al suggested that measuring ADAM17 activity may predict major cardiovascular events in subjects with established atherosclerosis (Rizza et al, 2015 ). Although ADAM17 activity was evaluated in an indirect manner through the measurement of its substrates in circulation, authors suggest that it is reasonable to assume that the increase in these molecules is related to increased ADAM17 activity in inflammatory sites.…”
Section: Adam17-mediated Growth Factors Signalingmentioning
confidence: 99%
See 1 more Smart Citation